THE INFLUENCE OF LIFESTYLE, BRAND IMAGE, COUNTRY OF ORIGIN ON PURCHASING DECISIONS WITH PRODUCT QUALITY AS INTERVENING - Janudin Janudin; Hestu Nugroho Warasto (Asosiasi Dosen Muda Indonesia, 2024)
This research aims to examine the influence of lifestyle, brand image, and Country of Origin on purchasing decisions for Samsung smartphone products, with product quality as an intervening variable. Data collection was carried out in South Tangerang during February 2024 using the Simple Random Sampling method with 125 respondents. Analysis was carried out using Structural Equation Modeling (SEM) with SmartPLS software version 3.0. The research results show that lifestyle has a positive and significant influence on consumer preferences and purchasing decisions regarding Samsung smartphone products. Brand Image also has a positive and significant influence on the perception of Samsung product quality, where product quality acts as a mediator between Brand Image and purchasing decisions. However, the country of origin of the product does not have a significant influence on consumer preferences and purchasing decisions. This shows that factors such as Brand Image, Lifestyle and Product Quality are more dominant in shaping consumer purchasing decisions regarding Samsung products.